From a Si3‐Cyclopropene to a Si3S‐Bicyclo[1.1.0]butane to a Si3S‐Cyclopropene to a Si3S2‐Bicyclo[1.1.0]butane: Back‐and‐Forth, and In‐Between. (25th September 2015) - Lee, Vladimir Ya.; Gapurenko, Olga A.; Miyazaki, Shogo; Sekiguchi, Akira; Minyaev, Ruslan M.; Minkin, Vladimir I.; Gornitzka, Heinz
Abstract: Compact and highly reactive bicyclo[1.1.0]butanes constitute one of the most fascinating classes of organic compounds. Furthermore, interplay of bicyclo[1.1.0]butanes with their valence isomers, such as buta‐1, 3‐dienes and cyclobutenes, is among the fundamental pericyclic transformations in organic chemistry. Herein we report the back‐and‐forth interconversion between the cyclotrisilenes and thiatrisilabicyclo[1.1.0]butanes, allowing for the synthesis of novel representatives of such classes of highly reactive organometallics. The peculiar structural and bonding features of the newly synthesized compounds, as well as the mechanism of their isomerization, were verified both experimentally and computationally. Abstract : Hin und her : Eine gegenseitige Umwandlung zwischen Cyclotrisilenen und Thiatrisilabicyclo[1.1.0]butanen ermöglicht die Synthese hoch reaktiver Organometallverbindungen. Struktur‐ und Bindungsverhältnisse der neu synthetisierten Verbindungen werden experimentell und theoretisch untersucht, ebenso der Mechanismus ihrer Isomerisierung.